Breast Angiosarcoma Surveillance Study: UK national audit of management and outcomes of angiosarcoma of the breast and chest wall. Issue 4 (22nd March 2021) - Banks, J; George, J; Potter, S; Gardiner, M D; Ives, C; Shaaban, A M; Singh, J; Sherriff, J; Hallissey, M T; Horgan, K; Harnett, A; Desai, A; et al.
Abstract: Background: Breast angiosarcomas are rare tumours of vascular origin. Secondary angiosarcoma occurs following radiotherapy for breast cancer. Angiosarcomas have high recurrence and poor survival rates. This is concerning owing to the increasing use of adjuvant radiotherapy for the treatment of invasive breast cancer and ductal cancer in situ (DCIS), which could explain the rising incidence of angiosarcoma. Outcome data are limited and provide a poor evidence base for treatment. This paper presents a national, trainee-led, retrospective, multicentre study of a large angiosarcoma cohort. Methods: Data for patients with a diagnosis of breast/chest wall angiosarcoma between 2000 and 2015 were collected retrospectively from 15 centres. Results: The cohort included 183 patients with 34 primary and 149 secondary angiosarcomas. Median latency from breast cancer to secondary angiosarcoma was 6 years. Only 78.9 per cent of patients were discussed at a sarcoma multidisciplinary team meeting. Rates of recurrence were high with 14 of 28 (50 per cent ) recurrences in patients with primary and 80 of 124 (64.5 per cent ) in those with secondary angiosarcoma at 5 years. Many patients had multiple recurrences: total of 94 recurrences in 162 patients (58.0 per cent). Median survival was 5 (range 0–16) years for patients with primary and 5 (0–15) years for those with secondary angiosarcoma. Development of secondary angiosarcoma had a negative impact on predicted breast cancer survival, with a median 10-year PREDICT prognostic rate of 69.6 per cent, compared with 54.0 per cent in the observed cohort. Conclusion: A detrimental impact of secondary angiosarcoma on breast cancer survival has been demonstrated. Although not statistically significant, almost all excess deaths were attributable to angiosarcoma. The increased use of adjuvant radiotherapy to treat low-risk breast cancer and DCIS is a cause for concern and warrants further study. Abstract : This paper presents findings from the UK Breast Angiosarcoma Surveillance Study (BRASS), a multicentre national collaborative audit resulting in 183 patient records. To date, this is the largest series published for secondary angiosarcoma and the second largest for primary angiosarcoma.